Arrhythmogenic Right Ventricular Cardiomyopathy in Pediatric Patients: An Important but Underrecognized Clinical Entity - te Riele, Anneline S. J. M.; James, Cynthia A.; Calkins, Hugh; Tsatsopoulou, Adalena (Frontiers in Pediatrics, 2021)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited cardiomyopathy characterized by fibrofatty infiltration of predominantly the right ventricular (RV) myocardium. Affected patients typically present as young adults with hemodynamically stable ventricular tachycardia, although pediatric cases are increasingly recognized. These young subjects often have a more severe phenotype with a high risk of sudden cardiac death (SCD) and progression towards heart failure. Diagnosis of ARVC is made by combining multiple sources of information as prescribed by the consensus-based Task Force Criteria. The description of Naxos disease, a fully penetrant autosomal recessive disorder that is associated with ARVC and a cutaneous phenotype of palmoplantar keratoderma and woolly hair facilitated the identification of the genetic cause of ARVC. At present, approximately 60% of patients are found to carry a pathogenic variant in one of five genes associated with the cardiac desmosome. The incomplete penetrance and variable expressivity of these variants however implies an important role for environmental factors, of which participation in endurance exercise is a strong risk factor. Since there currently is no definite cure for ARVC, disease management is directed towards symptom reduction, delay of disease progression, and prevention of SCD. This clinically focused review describes the spectrum of ARVC among children and adolescents, the genetic architecture underlying this disease, the cardio-cutaneous syndromes that led to its identification, and current diagnostic and therapeutic strategies in pediatric ARVC subjects.